ANALYSIS OF INTERNAL FACTORS AND EXTERNAL FACTORS OF BUKIT SIGUNTANG MARKETING - lidia wati; riska aryani; Ummasyroh (International Journal of Advanced Research in Social Studies, 2025)
This research aims to find out what the marketing strategy for tourist attractions is, as well as carrying out an analysis to determine the marketing of historical tourist attractions. Participants in this research were 30 visitors to Siguntang Hill. The approach used is a qualitative-descriptive approach with questionnaires as a data collection technique. The method used in this research is IFAS which consists of Strengths and Weaknesses factors, and EFAS which consists of Threats and Opportunities factors. The research results show that the internal factors of Bukit Siguntang tourism have greater strengths than their weaknesses, while the external factors of Bukit Siguntang tourism have equal opportunities and threats.